Pseudo-depth domain reverse time migration in VTI medium based on GPU parallel strategy - Xinwen, Zhang; Jianping, Huang; Zhiqiang, Jiang; Qingyang, Li; Zhenchun, Li (Frontiers in Earth Science, 2023)
As one of the main imaging methods, a lot of attention has been directed to reverse time migration anisotropic media, where we have to deal with multi-parameters representing the medium. However, reverse time migration still faces cost and memory limitations, especially in imaging high frequencies. To obtain high-resolution images useful for stratigraphic interpretation, a coordinate transformation strategy in transversely isotropic media with a vertical axis of symmetry (VTI) is utilized. The coordinate transformation converts the traditional depth domain imaging into pseudo-depth domain imaging. In addition, this paper uses the Graph Process Unit (GPU) parallel strategy and compares the imaging approach with conventional acoustic isotropy methods. By testing several models and field data, it concludes that, GPU parallel strategy can significantly improve the computational efficiency of imaging. Besides, the pseudo-depth domain method has obvious advantages in computational time and memory consumption. Moreover, considering anisotropy is more suitable for complex laminated layers.